2004
DOI: 10.1159/000080705
|View full text |Cite
|
Sign up to set email alerts
|

Can Erythropoietin Therapy Improve Survival?

Abstract: The presence of anaemia in patients with cancer is correlated with poor clinical outcome, a reduced tumour response to anticancer therapy and an increased risk of mortality. This observation has led to speculation as to whether treatment of anaemia can enhance survival rates. The majority of studies have suggested that erythropoietic therapy either does not change or improves disease-free and/or overall survival. Only two studies, one in breast cancer and the other in head and neck cancer, both of which used e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Although these studies did not note a survival difference among patients who did and those who did not receive rhEPO, they involved only a short course of treatment with rhEPO (often around 12 weeks), were not designed and powered to assess overall survival, and often resulted in the controls receiving rhEPO after the study was terminated, thus clouding a possible effect on overall survival [11]. A meta-analysis of randomized controlled trials of the use of rhEPO for anemia associated with cancer and cancer treatment noted an overall survival benefit for the use of rhEPO (adjusted hazard ratio = 0.81; 95% CI = 0.67–0.99) [12, 13]. However, the same authors recently published a meta-analysis which included 57 studies and over 9,000 patients [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies did not note a survival difference among patients who did and those who did not receive rhEPO, they involved only a short course of treatment with rhEPO (often around 12 weeks), were not designed and powered to assess overall survival, and often resulted in the controls receiving rhEPO after the study was terminated, thus clouding a possible effect on overall survival [11]. A meta-analysis of randomized controlled trials of the use of rhEPO for anemia associated with cancer and cancer treatment noted an overall survival benefit for the use of rhEPO (adjusted hazard ratio = 0.81; 95% CI = 0.67–0.99) [12, 13]. However, the same authors recently published a meta-analysis which included 57 studies and over 9,000 patients [14].…”
Section: Introductionmentioning
confidence: 99%
“…In those trials, decreased survival and increased tumor progression were observed in patients who received epoetin α or epoetin β compared with patients who received placebo. These outcomes were in contrast to many clinical trials, which demonstrated that erythropoiesis‐stimulating agents (ESAs) are safe and efficacious for the treatment of anemia in cancer patients 3, 4. These trials were criticized for poor study design and execution 4.…”
mentioning
confidence: 97%
“…From these data, it is concluded that in clinically and statistically well-designed studies, ESA therapy has no adverse effects on survival [55]. It produces the expected increase in Hb levels and hence lowers transfusion frequency.…”
Section: Safety Of Esas When Used As Indicatedmentioning
confidence: 82%